2020
DOI: 10.47626/1679-4435-2020-519
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in primary and secondary school teachers in southern Brazil

Abstract: Introduction: Burnout syndrome is a form of professional exhaustion to which teachers are particularly vulnerable. Objectives: To investigate the association between burnout syndrome and occupational factors in primary and secondary school teachers in Brazil. Methods: A quantitative study of 200 teachers was conducted using a demographic and occupational questionnaire as well as the Maslach Burnout Inventory to investigate burnout syndrome. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Regarding the workload, many studies have shown that workload (expressed in our study as long hours spent for preparation of materials to be delivered to the students and teaching preparatory students, who are at the beginning of the teen age and need more time to understand and do better job in studying) was closely related to burnout in the form of emotional exhaustion and depersonalization among teachers, including Saudi teachers (Santana et al, 2012;Chalghaf et al, 2019;Amri et al, 2020;Salvagioni et al, 2020;Cobo-Vazquez et al, 2021;Kalynychenko et al, 2021;Li et al, 2021;Melanda et al, 2021;Ribeiro et al, 2021). Moreover, the notion of burnout as a response to job demands has been supported by both selfreports of experienced stress and more objective assessments of demands, such as the number of students and number of working hours (Maslach, 2001;Perry et al, 2014;Peterson et al, 2019;Hart et al, 2020;Ndongo et al, 2020;Shah et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding the workload, many studies have shown that workload (expressed in our study as long hours spent for preparation of materials to be delivered to the students and teaching preparatory students, who are at the beginning of the teen age and need more time to understand and do better job in studying) was closely related to burnout in the form of emotional exhaustion and depersonalization among teachers, including Saudi teachers (Santana et al, 2012;Chalghaf et al, 2019;Amri et al, 2020;Salvagioni et al, 2020;Cobo-Vazquez et al, 2021;Kalynychenko et al, 2021;Li et al, 2021;Melanda et al, 2021;Ribeiro et al, 2021). Moreover, the notion of burnout as a response to job demands has been supported by both selfreports of experienced stress and more objective assessments of demands, such as the number of students and number of working hours (Maslach, 2001;Perry et al, 2014;Peterson et al, 2019;Hart et al, 2020;Ndongo et al, 2020;Shah et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…It is usually developed in response to poor working circumstances, interpersonal interactions, poor work management, and administration (Moueleu Ngalagou et al, 2019;Ndongo et al, 2020;Civilotti et al, 2021;Goldstein and Alesbury, 2021;Losung et al, 2021;Sener et al, 2021;Wirkus et al, 2021). It usually affects medical professionals, teachers, police officers, army soldiers, as well as many other professionals (Burki, 2020;Ndongo et al, 2020;Goldstein and Alesbury, 2021;Grupe et al, 2021;Llorca-Pellicer et al, 2021;Mák et al, 2021;Márquez et al, 2021;Ribeiro et al, 2021;Righi et al, 2021;Wirkus et al, 2021). The syndrome is characterized by various symptoms ranging from emotional to psychiatric, cognitive, and psychosomatic symptoms with different severities (Bauer et al, 2006;Schilling et al, 2019;Lass-Hennemann et al, 2020;Civilotti et al, 2021;Juczynski and Oginska-Bulik, 2021;Oginska-Bulik and Juczynski, 2021;Righi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that teachers who worked more than 40 h a week or had work overload were more likely to experience emotional exhaustion. Work overload and long hours are risk factors for the development of burnout [ 51 , 52 , 53 ]. Other studies have also indicated that the number of jobs, the number of students for whom teachers are responsible, and even the sex of teachers are risk factors for the development of burnout syndrome [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in subjective sleepiness, mood, and emotional processing (including the ability to read positive emotional expressions), as well as the decreased stress threshold, lead to increased stress responses [ 62 , 63 , 64 , 65 ]. Moreover, they are important risk factors for the development of burnout syndrome [ 51 , 52 , 53 ]. It is well documented that sleep disturbances are associated with burnout [ 39 , 40 , 41 ], although these analyses did not report prevalence according to burnout subscales, only by the total sleep quality score.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of tiredness or depletion are also included in the word. Burnout is a term used in the work place to describe work related stress, which provides for feelings of physical and mental tiredness, impatience, loss of interest in work and low self worth (Ribeiro et al, 2021). Burnout syndrome (BS), which is an undesirable psychological state marked by weariness, cynicism and feelings of lost professional efficacy, is one stress related consequence teachers may face (Arvidsson et al, 2016).…”
mentioning
confidence: 99%